1995
DOI: 10.1088/0953-4075/28/4/011
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization of Ba+ions due to creation of 4d hole states

Abstract: Photoion spectrometry has been applied to determine the relative photoionization yields of Ba+ ions around the 4d ionization threshold. A ground state Ba+ ion beam was merged with monochromatized synchrotron radiation over a length of 15 cm. Counting the number of doubly and triply charged ions produced in the interaction region, we have obtained partial photoion yields as a function of photon energy. Prominent peaks due to resonance Auger processes have been observed below the threshold. A giant resonance str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 16 publications
3
21
0
Order By: Relevance
“…The yield of Xe 2+ originates primarily from direct ionization of the outer 5p electrons and subsequent Auger decay is not possible. An analogous case exists for Ba + as discussed by Koizumi et al [24]. The cross section reaches much larger values in the region for the 4d → 5p transitions near 55 eV where three resonances appear (see figure 2).…”
Section: Photoionization Of the Xe + Ionsupporting
confidence: 70%
“…The yield of Xe 2+ originates primarily from direct ionization of the outer 5p electrons and subsequent Auger decay is not possible. An analogous case exists for Ba + as discussed by Koizumi et al [24]. The cross section reaches much larger values in the region for the 4d → 5p transitions near 55 eV where three resonances appear (see figure 2).…”
Section: Photoionization Of the Xe + Ionsupporting
confidence: 70%
“…Previous photoabsorption experiments on Ba, Ba 1 , and Ba 21 [12,13] Ba 1 is similar to that of Ba while the absorption spectrum of Ba 21 is completely different [12], revealing a significant increase of the 4d-oscillator strength for discrete transitions. Among several theoretical approximations [14][15][16][17][18][19][20] proposed to interpret the Ba 21 spectrum multiconfiguration Hartree-Fock calculations [15,16,19] have yielded the best agreement with the experimental results.…”
mentioning
confidence: 72%
“…Previous photoabsorption experiments on Ba, Ba 1 , and Ba 21 [12,13] found that the absorption of 273002-1 0031-9007͞01͞ 87(27)͞273002(4)$15.00…”
mentioning
confidence: 99%
“…The charge state and photoion spectra were studied for Ne [3,49], Ar [4,11,12,[50][51][52][53], Kr [5,6,33,[53][54][55][56], Xe [6,9,16,34,35,46,[57][58][59][60], and for all of them [61][62][63]. Also such spectra were investigated for lanthanides [7-9, 15, 32, 64-66], Mg [50,67], Al, Si, S, Ca, Fe [50], Cu [18], Sr [68], Ba [69], Au [70], Re [71], and Ta [71]. In [36] the ion charge distribution due to vacancy cascades following the K, L 1 , L 2 , and L 3 shell ionization were calculated by the Monte Carlo method for the atomic numbers Z = 10−60.…”
Section: Introductionmentioning
confidence: 99%